RemTech Expo 2015 - MediaGEO, Redazione (GEOmedia, 2015)
Remtech Expo 2015, September 23/25, the event on the remediation and redevelopment of the territory organized by Ferrara Fiere (partner the Region of Emilia-Romagna, sponsors Eni Saipem) .